LINGUISTIC REALIZATION OF THE LEXICAL UNIT “AYOL” IN UZBEK AND RUSSIAN POETIC TEXTS - Adilova Dilorom Kadirovna (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific article examines the linguistic realization of the lexical unit “Woman” in poetic texts written in Uzbek and Russian languages. We study the semantic, syntactic and stylistic features of this word in the context of poetry, and show its cultural and literary significance for Uzbek and Russian literary traditions. By researching various Uzbek and Russian poetic works, we aim to shed light on the similarities and differences in the depiction of "Woman" in the language and perform a comparative analysis.